Anthocyanins and color in grain and cob of peruvian purple corn grown in Jalisco, Mexico - Aguilar-Hernández, Ángel Daniel; Salinas Moreno, Yolanda; Ramírez-Díaz, José Luis; Alemán-de la Torre, Ivone; Bautista-Ramírez, Edgardo; Flores-López, Hugo Ernesto (Revista Mexicana de Ciencias Agrícolas, 2019)
The grain and cob (Zea mays L.) of purple corn are a source of pigments, which can replace artificial colors. The objective was to determine the effect of the environment (temperature) of seed production on the content of anthocyanins in grain (CATg) and cob (CATo) and its correlation in a purple corn population of Peru. Seed production environments were Tepatitlan and La Huerta, Jalisco, Mexico. The seeds of the two environments were sown in the S-S 2015 cycle in Tepatitlan, Jalisco. They were pollinated from 100 to 130 plants. At harvest, the healthy ears with the intense purple grain color were analyzed by CATg and CATo by spectrophotometry. An analysis of variance and correlation of Person was made. The environment of seed production significantly affected (p≤ 0.05) the contents of anthocyanins in grain and cob. The seed obtained in Tepatitlan (average temperature 19.1 °C) presented a CATg of 496.3 mg equivalents of cyanidin 3-glucoside in 100 g of dry sample, which was 57.6% higher than that of the seed from La Huerta (mean temperature 25.4 °C). The cob presented between 48 and 70% more anthocyanins than the grain and similar chromatographic profile between grain and cob. The correlation between the grain color variables and the CATg was not significant (p≥ 0.05). However, the negative correlation of the chroma value with CATo was highly significant (r= -0.5484**) so it could be an estimator of the CAT in this structure.